Efficacy of simultaneous infusion of tirofiban with intravenous thrombolysis in patients with acute anterior choroidal or paramedian pontine infarction: TITACIPPI study - Toudou-Daouda, Moussa; Soumah, Djibril; Bentamra, Leila; Aminou-Tassiou, Nana-Rahamatou; Baby, Mohamed; Lhermitte, Yann; Altarcha, Tony; Aghasaryan, Manvel; Smadja, Didier; Chausson, Nicolas (Frontiers in Neurology, 2026)
Background and purposeIntravenous thrombolysis combined with tirofiban (IVT plus tirofiban) has been reported to be more effective than IVT alone in preventing early neurological deterioration (END) and improving 3-month functional outcomes in patients with ischemic stroke. This study aimed to assess the radiological efficacy and safety of simultaneous (or within 60 min) IVT plus tirofiban versus IVT alone specifically in patients with anterior choroidal infarction (ACI) or paramedian pontine infarction (PPI), two subtypes with a high risk of END.MethodsWe conducted a single-center, retrospective study including consecutive patients aged ≥18 years treated during two distinct periods: one with standard IVT alone and one with IVT plus tirofiban. The primary endpoint was ≥20% reduction in lesion volume on 24-h diffusion-weighted imaging (DWI). Secondary endpoints included early clinical improvement at 24 h and 7 days (or discharge), functional independence [modified Rankin Scale (mRS) scores ≤2 and ≤1] at 3 months, and END. Safety outcomes included symptomatic intracranial hemorrhage (sICH) and major systemic bleeding (MSB). A subgroup analysis compared clinical outcomes in patients with “lesion reversal” versus patients with no “lesion reversal.”ResultsA total of 58 patients were analyzed (30 IVT plus tirofiban; 28 IVT alone). Lesion reversal ≥20% was more frequently observed in the IVT plus tirofiban group (adjusted odds ratio, 8.58; 95% CI, 2.09–35.28; p = 0.001). No significant differences were found between groups for END or 3-month functional outcomes (mRS ≤2 or ≤1). One non-fatal MSB occurred in the IVT alone group. No cases of sICH were observed in either group. Overall lesion reversal was significantly associated with better early and late outcomes, and with IVT plus tirofiban treatment.Discussion and conclusionThis study suggests that IVT plus tirofiban improves radiological outcomes and may be a promising therapeutic option in patients with ACI/PPI, without increasing the risk of bleeding compared to IVT alone.Clinical trial registrationClinicalTrials.gov, identifier NCT05733507.